Identifying novel neuromodulator targets of human cognition - Colwell, MJ (2024)
Impaired cognition is often overlooked in the clinical management of depression, despite being a principal modulator of perceived disability and quality of life within depression (Knight, Air, & Baune, 2018; Knight, Lyrtzis, & Baune, 2020; Koenig, Bhalla, & Butters, 2014; Naismith, Longley, Scott, & Hickie, 2007). There is an outstanding need for new treatments to address this unmet clinical need: this thesis focuses on the identification of novel neuromodulator targets of human cognition which offer therapeutic promise for cognitive impairment in depression. Chapter 1 of this thesis reviews the evidence which supports the pharmacological targeting of impaired cognition in individuals with depression. This review was informed by interviews (PPI consultations) with individuals with lived experience of depression, helping shape research priorities within this thesis. As a result of this review, promising targets of cognitive function in humans were identified for investigation, including the serotoninergic and histaminergic system. In Chapters 2 and 3, we use a unique approach to increasing synaptic serotonin levels in humans – a selective serotonin releasing agent – to examine its effect on human cognition and emotional processing. In Chapters 4 and 5, the effects of histamine autoreceptor blockade on cognition and neural dynamics in humans are explored. The research covered in Chapters 2–5 employs an experimental medicine approach, where healthy volunteers are used to model the cognitive effects of pharmacological interventions to assess their viability for clinical translation. Chapter 6, the final chapter, unifies the research findings reported within this thesis, placing them in a broader literature context, with suggestions for potential directions of travel for future research. The experimental findings presented in this thesis provide a foundation for future translational research to explore the therapeutic potential of these drug mechanisms within clinical populations.